1990
DOI: 10.1213/00000539-199008000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pain Control With a Continuous Infusion of Epidural Sufentanil in the Intensive Care Unit

Abstract: A prospective, randomized, double-blind trial was conducted to compare the analgesic actions and side effects of sufentanil continuously infused (5 micrograms/h) into the lumbar epidural space (L2-3) with those of an infusion of lumbar epidural morphine (0.5 mg/h). Forty patients admitted to an intensive care unit after elective major abdominal surgery participated over a varying period of 24-40 h. Post-operative pain was treated with an epidural bolus of either sufentanil (50 micrograms) or morphine (5 mg), f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…These isolated findings did not persist when studies were pooled overall and in subgroup analysis by type of surgery. Importantly, the use of analgesic adjuncts was similar between groups (for all but 2 trials), 23,42 as was overall total opioid consumption. Several factors may account for this lack of difference in analgesia.…”
Section: Analgesiamentioning
confidence: 84%
See 2 more Smart Citations
“…These isolated findings did not persist when studies were pooled overall and in subgroup analysis by type of surgery. Importantly, the use of analgesic adjuncts was similar between groups (for all but 2 trials), 23,42 as was overall total opioid consumption. Several factors may account for this lack of difference in analgesia.…”
Section: Analgesiamentioning
confidence: 84%
“…41 Adjuncts to Analgesia Dyer et al 23 reported significantly higher use of supplementary IV morphine in the epidural sufentanil group compared with the epidural morphine group. In addition, despite detecting no difference in VAS pain scores, the pediatric study by Cho et al 42 showed that patients in the fentanyl group required more rescue analgesia than those receiving sufentanil (6/32 subjects compared with 0/32 subjects; P = 0.012).…”
Section: Individual Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The adverse effects of epidural analgesics reported in the literature include nausea and vomiting, pruritus, urinary retention, ileus formation, respiratory depression, oversedation, hypotension, motor block and neurological complications (9)(10)(11)(12)(13). The dosages of EM and fentanyl, as well as the administration of EM as a bolus, would contribute to the relatively high prevalence of side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The main application route of spinal epidural opioids remains the epidural catheter with single bolus doses or continuous infusion [15,17,19,20,51,52]. The level of drug concentration in the infusion is higher than the plasma level, thus allowing selective analgesia and avoiding major complications due to systemic drug actions [46,53].…”
Section: Discussionmentioning
confidence: 99%